2020
DOI: 10.3390/catal10091048
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Reduction of NOx by CO over Doubly Promoted MeMo/Nb2O5 Catalysts (Me = Pt, Ni, or Co)

Abstract: Doubly promoted MeMo/Nb2O5 catalysts, in which Me = Pt, Ni, or Co oxides were prepared for the selective catalytic reduction of NOx by CO reaction (CO-SCR). Comparable chemical, textural, and structural analyses revealed similarities between NiMo and CoMo impregnated on Nb2O5, in contrast to PtMo sites, which were not homogeneously dispersed on the support surface. Both the acid function and metal dispersion gave a synergistic effect for CO-SCR at moderate temperatures. The reactivity of PtMo catalysts towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 51 publications
4
16
0
Order By: Relevance
“…Reduction of metal nanoparticles is assumed to be produced by the sonolysis of metal precursors based on the cavitation effects. 24,49 The adhesion behavior of metal nanoparticles on BNNT is similar to the previously reported results even with the different supports, surface metals, and synthesis methods. 50,51 The TEM images for Pd/BNNT (panels a and b of Figure 2) showed that aggregated Pd nanoparticles are located at the surface of the BNNT.…”
Section: Catalyst Synthesis and Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…Reduction of metal nanoparticles is assumed to be produced by the sonolysis of metal precursors based on the cavitation effects. 24,49 The adhesion behavior of metal nanoparticles on BNNT is similar to the previously reported results even with the different supports, surface metals, and synthesis methods. 50,51 The TEM images for Pd/BNNT (panels a and b of Figure 2) showed that aggregated Pd nanoparticles are located at the surface of the BNNT.…”
Section: Catalyst Synthesis and Characterizationsupporting
confidence: 88%
“…29,31−35 Among different support materials, it was reported that the BN materials exhibit excellent stability and catalytic efficiency when combined with metal nanoparticles. 24,36 The excellent remedy of the defects and vacancies in BN-based materials using CO and NO gases also correlates with their good adsorption properties. 37,38 Hence, BN-based materials are worth considering as an affordable catalyst for enhancing the NO + CO reaction.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In response to the contradiction, the current result illustrates that the expected NTs performance with NO x conversion is superior to 20%, even upon steam introduction ( Figure 7 a). Thus, moisture interacts with the surface of the NTs and modifies the surface-active sites and the distribution of Lewis and Brønsted acid sites, as found elsewhere [ 59 ]. Meanwhile, a steep plateau in the NO x conversion is seen in CoNT catalyst with prolonged reaction time due to Co sites oxidation by water vapor.…”
Section: Resultsmentioning
confidence: 82%
“…It is worth mentioning that PM/Nb is a sintering-resistant solid due to the strong metal–support appearing between Pt and the Nb–O–Mo support, and thus, the catalytic activity during TRM is maintained compared with NM/Nb and CM/Nb (Figure and Figure ). This can be evidenced from the fact that the well-dispersed Pt nanoparticles in close contact with Mo/Nb 2 O 5 split into PtO x and the other alloy between Mo and Pt . Moreover, the reasons for the superior catalytic activity of PM/Nb are not clear at this point, since catalytic performance is 1 to 2 orders of magnitude higher than that on the PM/LaAl catalyst.…”
Section: Resultsmentioning
confidence: 99%